An alternate synthesis of appetite suppressant (R)-2-benzylmorpholine employing Sharpless asymmetric epoxidation strategy. Issue 8 (24th February 2016) - Viswanadh, N.; Mujumdar, P.; Sasikumar, M.; Kunte, S.S.; Muthukrishnan, M.
Graphical abstract: Abstract: An alternate synthesis of ( R )-2-benzylmorpholine1, an appetite suppressant agent has been accomplished starting from readily available trans -cinnamyl alcohol employing Sharpless asymmetric epoxidation strategy as a key step, with an overall yield of 24%.